Mesoscale hydrological variability induced by northwesterly wind on the French continental shelf of the Bay of Biscay - Puillat, Ingrid; Lazure, Pascal; Jegou, Anne-Marie; Lampert, Luis; Miller, Peter (Scientia Marina, 2006)
On the French continental shelf of the Bay of Biscay the variability of the surface salinity distribution has been mainly investigated at the seasonal and inter-annual scales. Here, new mesoscale features such as lower-salinity lenses observed in model results are investigated by hydrological measurements acquired during 8 cruises (1997-2000). These lenses are 50-80 km wide and 30 m thick and occur during westerly to northerly wind events that push offshore the less saline water of river plumes. These water masses detached from the coast are replaced with upwelled saltier water at the coast, so coastal upwelling is often observed at the same time along Landes and southern Brittany coasts. We show that in addition to the influence of seasonal and inter-annual variability of the wind and river outflows, short term meteorological variability may drive mesoscale structures on this continental shelf.